Soil microbial responses to multiple global change factors as assessed by metagenomics - Álvaro Rodríguez del Río; Stefan Scheu; Matthias C. Rillig (Nature Communications)
Abstract Anthropogenic activities impose multiple concurrent pressures on soils globally, but responses of soil microbes to multiple global change factors are poorly understood. Here, we apply 10 treatments (warming, drought, nitrogen deposition, salinity, heavy metal, microplastics, antibiotics, fungicides, herbicides and insecticides) individually and in combinations of 8 factors to soil samples, and monitor their bacterial and viral composition by metagenomic analysis. We recover 742 mostly unknown bacterial and 1865 viral Metagenome-Assembled Genomes (MAGs), and leverage them to describe microbial populations under different treatment conditions. The application of multiple factors selects for prokaryotic and viral communities different from any individual factor, favouring the proliferation of potentially pathogenic mycobacteria and novel phages, which apparently play a role in shaping prokaryote communities. We also build a 25 M gene catalog to show that multiple factors select for metabolically diverse, sessile and non-biofilm-forming bacteria with a high load of antibiotic resistance genes. Finally, we show that novel genes are relevant for understanding microbial response to global change. Our study indicates that multiple factors impose selective pressures on soil prokaryotes and viruses not observed at the individual factor level, and emphasizes the need of studying the effect of concurrent global change treatments.